Pengggunaan Media Belajar dalam Memotivasi Siswa - Samsu Armadi (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2019)
This study gives expression to the correlation of medium of instruction to learning motivation of the students. Product Moment was used to analize the data. The findings of the study were revealed that a significant correlation was proven by medium of instruction (X) to learning motivation (Y) with the correlation coefficient r = 0.642 that was greater (>) than r-table 0.235 at the significance level 0.05 and N = 72. It meant that the more medium of instruction usage was good, learning motivation of the students became more and more raising, too.